Propuesta para enseñar y aprender matemática a distancia desde un abordaje novedoso de los Programas de Estudio - Rojas Jiménez, Yorleny (2020)
The context is described to clarify the work environment in which the proposal was born from Costa Rica’s Ministry of Public Education’s framework for the 2020 school year, Ministry of Public Education of Costa Rica and its continuity, in relation to the progress of the COVID- 19 pandemic crisis and ministerial decisions to face it through the telework of civil servants and distance education. Subsequently, part of the daily work of the Mathematics pedagogical consultancy of the Regional Directorate of Education of San Carlos is detailed, regarding the progress of the school year, which allows the proposal of premises and reformulations on the work carried out in distance education. In this way, the proposal to teach and learn mathematics at a distance was born, which takes as its main basis a sufficient approach to mathematics study programs (MEP, 2012), using techniques and strategies that favor teaching that takes into account instructional planning, methodology and evaluation for learning, with projection for later use. Finally, the conclusions are presented, which contrast the problems that arise as a result of the COVID-19 pandemic with respect to distance education, with the premises that feed the proposal and the model that allows its justification.